Crowding-induced morphological changes in synthetic lipid vesicles determined using smFRET - Quinn, Steven D.; Dresser, Lara; Graham, Sarah; Conteduca, Donato; Shepherd, Jack; Leake, Mark C. (Frontiers in Bioengineering and Biotechnology, 2022)
Lipid vesicles are valuable mesoscale molecular confinement vessels for studying membrane mechanics and lipid-protein interactions, and they have found utility among bio-inspired technologies including drug delivery vehicles. While vesicle morphology can be modified by changing the lipid composition and introducing fusion or pore-forming proteins and detergents, the influence of extramembrane crowding on vesicle morphology has remained under explored owing to a lack of experimental tools capable of capturing morphological changes on the nanoscale. Here, we use biocompatible polymers to simulate molecular crowding in vitro, and through combinations of FRET spectroscopy, lifetime analysis, dynamic light scattering and single-vesicle imaging, we characterize how crowding regulates vesicle morphology. We show that both freely-diffusing and surface-tethered vesicles fluorescently tagged with the DiI and DiD FRET pair undergo compaction in response to modest concentrations of sorbitol, polyethylene glycol and Ficoll. A striking observation is that sorbitol results in irreversible compaction, whereas the influence of high molecular weight PEG-based crowders was found to be reversible. Regulation of molecular crowding allows for precise control of vesicle architecture in vitro, with vast implications for drug delivery and vesicle trafficking systems. Furthermore, our observations of vesicle compaction may also serve to act as a mechanosensitive readout of extramembrane crowding.